Пошаговое объяснение:
x²+6x+5=0
D=36-20= 16
x1= (-6-4)/2= -5
x2= (-6+4)/2= -1
x²+x-12=0
D=1+48= 49
x1= (-1-7)/2= -4
x2= (-1+7)/2= 3
х²+6х+5=0
а=1, b=6, c=5
D=b²-4ac
D=(6)²-4*1*5=36-20=16=4²
x₁=(-b+√D)/2a=(-6+4)/2=-2/2=-1
x₂=(-b-√D)/2a=(-6-4)/2=-10/2=-5
х²+х-12=0
а=1, b=1, c=-12
D=(1)²-4*1*(-12)=1+48=49=7²
x₁=(-b+√D)/2a=(-1+7)/2=6/2=3
x₂=(-b-√D)/2a=(-1-7)/2=-8/2=-4
Пошаговое объяснение:
x²+6x+5=0
D=36-20= 16
x1= (-6-4)/2= -5
x2= (-6+4)/2= -1
x²+x-12=0
D=1+48= 49
x1= (-1-7)/2= -4
x2= (-1+7)/2= 3
х²+6х+5=0
а=1, b=6, c=5
D=b²-4ac
D=(6)²-4*1*5=36-20=16=4²
x₁=(-b+√D)/2a=(-6+4)/2=-2/2=-1
x₂=(-b-√D)/2a=(-6-4)/2=-10/2=-5
х²+х-12=0
а=1, b=1, c=-12
D=b²-4ac
D=(1)²-4*1*(-12)=1+48=49=7²
x₁=(-b+√D)/2a=(-1+7)/2=6/2=3
x₂=(-b-√D)/2a=(-1-7)/2=-8/2=-4